Comparison of ERS′93 to the newly published GLI′17 reference values for carbon monoxide transfer factor. (January 2019) - Oostveen, Ellie; Derom, Eric; Vints, Anne-Marie; Liistro, Giuseppe
Abstract: Background: The new predicted values for the carbon monoxide transfer factor (TL, CO) for Caucasians by the Global Lung Function Initiative are available since September 2017. Several authors have previously shown that the predicted values of Cotes et al. (ERS′93), overestimated TL, CO. However, the GLI′17 authors omitted to compare their predicted values with the ERS′93 equations, still in use throughout Europe. We present the differences between the two sets of predicted values, and in an attempt to improve the readability, used the contour plots instead of the classical 2-dimensional representations. Methods: Predicted values were computed for males and females for ages between 18 and 70 years and heights between 155 and 180 cm using Matlab software with increments of one unit (1 yr, 1 cm). Results: We demonstrate that GLI-'17 predicted values of TL, CO are systematically lower than those of ERS-'93, but also that the magnitude of the differences varies according to age, height and sex. More specifically, differences increase in both males and females by decreasing age and height, reaching up to 16% in males and 24% in females. Conclusion: The predicted values of TL, CO by Cotes at al. are systematically larger than the new GLI'17 values. Plotting all the possible differences between predicted variables using contour graphs allows to identify the groups of subjects in whom significant changes in their predicted values will occur. Our findings should prompt physicians to investigate how switching to GLI-17 equations affects the clinical interpretation of TL, CO measurements in a real-live setting. Highlights: GLI-'17 predicted values of TL, CO are systematically lower than those of ERS-'93. False-positive risk of decreased TL, CO using ERS-'93 increases in young and short females. Contour plot improves legibility of graphs presenting differences between reference values.